ANALISIS TES IMUNOKROMATOGRAFI DAN ENZYME-LINKED IMMUNOSORBENT ASSAY UNTUK MENDETEKSI Helicobacter pylori DI PASIEN DISPEPSIA - I Hutagalung; Uleng Bahrun; Mansyur Arif; Rifai Amirudin; HAM Akil (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Many methods are available to diagnose Helicobacter pylori in patients with dyspepsia, including Enzyme-Linked ImmunosorbantAssay (ELISA) and recently used is immnochromatography test. Both of the test are non invasive method, but immunochromatographytest can be used in laboratory without semi automatic analyzer. The aim of this study was to compare the immunochromatographyand ELISA tests in detecting the possibility of Helicobacter pylori infection. A cross sectional study was done among 49 sampleswith dyspepsia at Wahidin Sudirohusodo Hospital of Makassar and Prodia Laboratory from March to August 2008. Samples wereanalyzed with SPSS 14 for Windows Program using Chi Square and Spearman correlation tests. Among 49 samples we found ELISAand immunochromatography tests were positive in 5 samples, ELISA and immunochromatography tests were negative in 33 samples,ELISA tests were borderline and immunochromatography tests were positive in 5 samples, and ELISA tests were borderline andimmunochromatography tests were negative in 6 samples. There was a good correlation between ELISA and immunochromatographytest with R = 1.000 and p = 0.000. Both results of the immunochromatography and ELISA tests showed high conformity. Both methodcan be applied to diagnose Helicobacter pylori in patients with dyspepsia. Immunochromatography test can be an alternative methodin laboratories who do not apply semi automatic analyzer. The advantages of immunochromatography test can be used for diagnoseearly infection of Helicobacter pylori.